3D Printing of Metal - Zhao, Zhanyong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Metal 3D printing, as an advanced forming, can manufacture parts directly from digital model by using layer by layer material build-up approach. This manufacturing method can prepare complex shape metal parts in short time, with and high precision. Three-dimensional printing processes can be classified into two major groups: Powder Bed Fusion-based technologies and Directed Energy Deposition. Three-dimensional printing features freedom of part complexity, part design, and light-weighting for aerospace, automobile, and other industries application. The Global Metal 3D Printing Market is mainly driven by the the fast developing of aerospace and automobile industry. The Global Metal 3D Printing Market size was valued at USD 534.18 Million in 2020 and is projected to reach USD 4458.76 Million by 2028, growing at a CAGR of 30.38% from 2021 to 2028.